Spectral Theory and Quantum Mechanics : Mathematical Foundations of Quantum Theories, Symmetries and Introduction to the Algebraic Formulation /: Mathematical Foundations of Quantum Theories, Symmetries and Introduction to the Algebraic Formulation. (2018) - Moretti, Valter
No abstract available